A study of the overtopping breach of a sand-gravel embankment dam using experimental models. (June 2021) - Li, Yanlong; Tian, Chao; Wen, Lifeng; Chen, Anke; Wang, Lin; Qiu, Wen; Zhou, Heng
Highlights: Overtopping breach experiments of sand-gravel dam without face slab were conducted. The breaching process can be roughly divided into four stages. The high phreatic line and large saturation zone intensifies dam breathing process. The drainage zone in sand-gravel dam can effectively restrain the dam breach process. Abstract: Sand-gravel embankment dams are increasingly being built using sand and gravel as these materials provide advantageous characteristics of a large compressive modulus and small porosity. Floods, landslides, and seismic surge waves can result in dam overtopping, which may further result in a breach of a sand-gravel embankment dam. Many factors affect the breaching process of a sand-gravel embankment dam, including the failure of the anti-seepage face slab and the initial seepage field. This study conducted overtopping breach experiments of a sand-gravel embankment dam without an upstream face slab to study the breaching process and identify the influence of the initial seepage field and drainage zone. Experimental models of sand-gravel embankment dams with three different initial seepage fields were established. The breach flow, breach expansion processes, and pore water pressure during the breaching process were observed. The results showed that the breaching process can be roughly divided into four stages: (1) downstream dam slope erosion; (2) gully expansion; (3) breach expansion and; (4) breach stabilization. The high phreatic line and large saturation zone intensified the dam breaching process, which aggravated breach expansion, increased the peak flow, and shortened the breach duration. The drainage zone in a sand-gravel embankment dam effectively restrained the dam breach process.